The Effect of the Implementation of the Cooperative Learning Model Type Student Teams Achievement Division (STAD) on Creativity, Initiative, Motivation and Student Learning Outcomes - Arsil; Hamengkubuwono; Abdul Rahman (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
This study investigates the implementation and impact of the Student Teams Achievement Division (STAD) cooperative learning model in the Islamic Cultural History (Sejarah Kebudayaan Islam/SKI) curriculum at Madrasah Tsanawiyah (MTs) in Rejang Lebong Regency. The objectives are twofold: (1) to describe the application of the STAD model in classroom settings, and (2) to analyze its influence on students’ creativity, initiative, motivation, and learning outcomes. Employing a quantitative research design, data were collected from a sample of 35 students using validated and reliable questionnaires. These instruments measured key variables such as creativity, initiative, motivation, and academic performance. Statistical analysis revealed that the STAD model significantly enhances students’ creativity, initiative, and motivation. Although a positive trend was observed in learning outcomes, its impact was comparatively moderate. The findings underscore the effectiveness of structured cooperative learning in promoting active engagement and supporting the development of 21st-century competencies within the SKI subject area. The study concludes that STAD is a valuable pedagogical strategy that benefits student-centered learning but recommends adaptations for optimal outcomes. Suggested improvements include rotating student roles within teams, integrating holistic assessment tools, providing teacher training in group facilitation, implementing project-based learning activities, and incorporating contextual Islamic case studies to enrich content relevance and critical thinking.